Inside the UDA : volunteers and violence - Crawford, Colin, 1948- (Pluto Press, 2003)
Providing an insight into the beliefs and political ideology of the Ulster Defence Assocation (UDA) and the Ulster Freedom Fighters (UFF), this book features interviews with key members of these paramilitary groups, many conducted inside the Maze prison.